Investment outlook for the medium range tanker segment from the perspective of a ship financier from 2011 to 2015 - Ma, Aiping (2011)
This research is to provide the freight market outlook for the MR product tanker segment in the East of Suez market from 2011 to 2015 and determine whether investors should venture into this shipping market segment.